THE MORPHOLOGY OF THE STRUCTURAL PARTS OF THE DIAPHRAGM 14 DAYS AFTER APPLICATION OF STANDARD INTRA-ABDOMINAL PRESSURE IN LAPAROSCOPIC SURGERY: AN EXPERIMENTAL STUDY - Dzyubanovsky, Ihor Ya.; Kritsak, Myroslav Yu.; Dzyubanovsky, Oleh I.; Gargula, Tetiana I.; Burak, Andrii Ye. (Eastern Ukrainian Medical Journal, 2025)
Introduction. In the course of laparoscopic surgery, carbon dioxide is injected into the abdominal cavity in order to create a working space through pneumoperitoneum. The increase in intra-abdominal pressure leads to an upward displacement of the diaphragm, increased airway pressure and decreased chest wall compliance, and a decrease in lung volume.Materials and Methods. The experimental study was performed on 30 mature rats, which were divided into two groups of 15 animals each.The animals underwent the creation of a pneumoperitoneum of standard pressure in laparoscopy under general anaesthesia for a period of 5 hours.In the first group, the diaphragm was sampled immediately after 5 hours.In the other group, the diaphragm was sampled 14 days after the created pneumoperitoneum. The costal, lumbar, and tendon parts of the diaphragm were taken separately and placed in 10% formalin for further histological examination.Results. Following a 5-hour pneumoperitoneum, observations were made of muscle deformation, fragmentation and lysis in muscle parts, and an increase in fibre heterogeneity. In transverse sections, muscle fibres became rounded and reduced in diameter. In response to the damage, cellular inflammatory infiltrates appeared, and a distinctive feature was the presence of haemorrhagic infiltration. In the lumbar region, significant changes were observed in the arterial vessels: the endothelium was exfoliated and freely located in bloodless lumens. The arterial wall exhibited thickening, the boundaries between its layers became indistinct, and the myocytes manifested a vacuolated appearance. The presence of oedema and polymorphonuclear cell infiltrates, as well as proliferating connective tissue, was observed in the perivascular area.In the tendon part, the lesion area exhibited multiple foci of destruction, which were infiltrated by lymphocytes and macrophages, accompanied by oedema of the underlying substance.The data obtained from the second group revealed a heterogeneous morphological picture, characterised by areas of normal structure and areas exhibiting partial loss of muscle layer compactness. The sarcoplasm was found to be heterogeneous, with foci of oedema and disintegration, and transverse striations in these foci were not visualised. The nuclei retained their typical location within the skeletal muscle. The connective tissue of the endomysium and perimysium exhibited uneven thickness, attributable to edematous loosening and proliferation. Perivascular fibrosis was pronounced, and the haemocirculatory bed was observed to be uniformly filled with blood. Small-calibre arteries contained a limited number of red blood cells or were found to be empty. A similar heterogeneity was observed in the tendons, which exhibited both an ordered compact arrangement of collagen fibres and areas of loosening and fragmentation.Conclusions. The results obtained allow the conclusion to be drawn: 14 days after the implementation of pneumoperitoneum, there is an incomplete structural recovery of the muscle and tendon component of the diaphragm of experimental animals. This is evidenced by replacement fibrosis in areas of muscle fibre damage, an increase in the amount of adipose tissue in the stroma, and a loosening of collagen fibres. These changes cannot lead to diaphragmatic dysfunction.